How High‐Commitment HRM Relates to Engagement and Commitment: The Moderating Role of Task Proficiency. Issue 3 (25th April 2014) - Boon, Corine; Kalshoven, Karianne
<x xml:space="preserve">Abstract</x> In a multisource field study, we examine the relationship between employee perceptions of high‐commitment human resource management (HRM), task proficiency, work engagement, and organizational commitment. Based on conservation of resources (COR) theory, we first propose that work engagement mediates the relationship between high‐commitment HRM and organizational commitment. Second, we propose a mediated moderation model in which employees' task proficiency moderates the relationship between high‐commitment HRM and work engagement, which in turn affects organizational commitment. Results indicate that the relationship between high‐commitment HRM and organizational commitment was fully mediated by work engagement. Results also supported the mediated moderation model. A significant indirect effect was found from high‐commitment HRM to commitment via engagement for low task proficiency, but not for high task proficiency. Implications and directions for future research are discussed. © 2014 Wiley Periodicals, Inc.